MANAGEMENT OF ISLAMIC EDUCATION LEARNING IN TPA ACTIVITIES AT THE NURUL IMAN PAKEM MOSQUE - Hasanah, Nur Zaytun; Istiqomah, Istiqomah (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This research is motivated by the weak interest in learning children in religious education. In fact, in almost all places, many TPAs no longer organize teaching and learning activities because there are no teachers, so learning management in TPA based on Islamic education is very much needed. This study aims to interpret the management of Islamic education learning in TPA activities at the Nurul Iman Pakem Mosque. This research is a type of qualitative research with a qualitative descriptive research approach. Data collection techniques used are observation methods, documentation methods, and interview methods. The data analysis technique used is Miles, Huberman, and Saldana with the stages of data collection, data condensation, data presentation, and drawing conclusions. The results of the study show that learning management in TPA activities at the Nurul Iman Mosque has been going well and its implementation is in accordance with Islamic education. By taking steps according to the principles of management implementation, namely planning, organizing schedules, implementing Islamic education-based learning, as well as monitoring and evaluation.